The relationship of market sentiment and sector return across time and frequency – a wavelet coherence analysis - Patel, Versha; Amilan, S.; Vairasigamani, P (The Economics and Finance Letters, 2025)
Investment diversification is a strategic approach to mitigating risks by spreading assets across various sectors. Each sector has its unique temperament when it comes to market sentiment. Certain sectors are more prone to being influenced by sentiment, while others are less so. Conventional approaches often overlook the dynamic interaction between market sentiment and sector returns. The study utilized data from the Bombay Stock Exchange and National Stock Exchange, including all sectoral indices of the BSE from April 2008 to June 2023. A composite sentiment index was developed using Principal Component Analysis. The study employed Wavelet coherence to measure the association between market sentiment and stock returns of different sectors across time and frequency domains. The findings reveal that non-cyclical sectors like Tech, Health, IT, Telecom, Energy, and FMCG exhibit less sensitivity to fluctuations in sentiment and are less volatile, as these sectors provide indispensable services. Sectors such as Commodities, Financial Services, Industrial, Metal, and Auto show stronger coherence with sentiment, as they exhibit cyclical patterns and are connected with economic circumstances, making them more prone to market volatility. These insights help institutional investors and portfolio managers develop risk-adjusted strategies, align investments with risk tolerance, and balance short-term sentiment analysis with long-term fundamentals.